STUDI KOMPARASI ANTARA ANALISIS DUA DIMENSI (2D) DAN TIGA DIMENSI (3D) PADA STRUKTUR GEDUNG BERTINGKAT 14 STUDI KASUS HOTEL HOLIDAY INN EXPRESS SEMARANG - Galih Widyarini; Lisatia Dian Pithaloka; Sukamta Sukamta; Parang Sabdono (Jurnal Karya Teknik Sipil, 2013)
Analysis of the structure is one important thing in planning the structure, particularly the structure of the building. There are two ways to analyze the structure, structural analysis of 2D and 3D structural analysis, with using computer program SAP2000 to get the value and direction of the force used in designing the structure. Comparative study of the structural analysis of 2D and 3D structural analysis is doing on  the existing structure Inn Express Hotel (HIEX) Semarang, that have purpose to compare the output styles, knowing the advantages and disadvantages of both ways, and counting the moment capacity. The results of the analysis of the structure of the results obtained is the difference in styles between 2D and 3D is relatively small with the analysis of 2D structures larger than the 3D.